2021
DOI: 10.1017/s0267190520000148
|View full text |Cite
|
Sign up to set email alerts
|

Brain, musicality, and language aptitude: A complex interplay

Abstract: Music and language are highly intertwined auditory phenomena that largely overlap on behavioral and neural levels. While the link between the two has been widely explored on a general level, comparably few studies have addressed the relationship between musical skills and language aptitude, defined as an individual's (partly innate) capacity for learning foreign languages. Behaviorally, past research has provided evidence that individuals’ musicality levels (expressed by singing, instrument playing, and/or per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 80 publications
0
8
0
Order By: Relevance
“…In the present model, the starting point of language aptitude is the auditory cortex (HG), which in previous studies was found to be a neuroanatomical marker for individual differences in speech sound learning and phonetic experience (Golestani et al, 2002(Golestani et al, , 2007(Golestani et al, , 2011, language aptitude (Turker et al, 2017(Turker et al, , 2019; see also discussion in Turker & Reiterer, 2021) and musical aptitude (Benner et al, 2017;Seither-Preisler et al, 2014). Since interindividual variation of the auditory cortex can be even observed at a prenatal stage, this cortical structure bears the potential to boost auditory processing for speech and language learning from very early periods on.…”
Section: The Neural Basismentioning
confidence: 91%
See 2 more Smart Citations
“…In the present model, the starting point of language aptitude is the auditory cortex (HG), which in previous studies was found to be a neuroanatomical marker for individual differences in speech sound learning and phonetic experience (Golestani et al, 2002(Golestani et al, , 2007(Golestani et al, , 2011, language aptitude (Turker et al, 2017(Turker et al, , 2019; see also discussion in Turker & Reiterer, 2021) and musical aptitude (Benner et al, 2017;Seither-Preisler et al, 2014). Since interindividual variation of the auditory cortex can be even observed at a prenatal stage, this cortical structure bears the potential to boost auditory processing for speech and language learning from very early periods on.…”
Section: The Neural Basismentioning
confidence: 91%
“…Musicality has also been shown to impact language learning (see recent review on interactions between language aptitude and music on the neural level by Turker & Reiterer, 2021). In the early stages of language learning, infants are acutely sensitive to prosodic patterns, which enable later phonological development (Gervain & Mehler, 2010).…”
Section: The Role Of Cognitive Abilities Musicality and Memory During Language Learningmentioning
confidence: 99%
See 1 more Smart Citation
“…"This is most likely caused by the large neural overlap between language and music, specifically the potential of music (through musical training or already present high musicality) to enhance language-relevant skills (e.g. auditory discrimination, attention, memory)" (Turker & Reiterer 2021).…”
Section: Musicality and Language Learning Abilitiesmentioning
confidence: 99%
“…Some theorists (e.g., Patel, 2011Patel, , 2014Tierney & Kraus, 2013) propose that formal music training improves language ability, focusing on transfer from music to language. Others consider overlapping genetic contributions and neural substrates (Nayak et al, 2022;Sammler & Elmer, 2020;Turker & Reiterer, 2021), acknowledging that natural musical ability influences who takes music lessons.…”
mentioning
confidence: 99%